Effect of healthcare on mortality: trends in avoidable mortality in Umbria, Italy, 1994-2009 - Fabrizio Stracci; Fortunato Bianconi; Giuseppe Michele Masanotti; Valerio Brunori; Francesco La Rosa (Istituto Superiore di Sanità, 2013)
OBJECTIVE: Avoidable mortality trends over the period 1994-2009 were calculated to evaluate health intervention by the health system of Umbria, a region of central Italy. MATERIALS AND METHODS: Mortality data were supplied by the regional causes of death registry. Rates were standardized to the 2001 census Italian population. Joinpoint regression was used to analyze the trends. RESULTS: Overall avoidable mortality rates decreased significantly both in males (-3.9% per year) and in females (-3.6% per year). Mortality rates from ischemic heart and cerebrovascular disease about halved in the study period in both sexes. Avoidable mortality increased slightly only for a few causes (e.g. lung cancer in females). CONCLUSION: The overall trend of avoidable mortality indicates that the regional health/ preventive system is performing well.